KEBIJAKAN DAERAH DIBIDANG PERDAGANGAN YANG MENYEBABKAN EKONOMI BIAYA TINGGI - Firman Mutakin (Buletin Ilmiah Litbang Perdagangan, 2008)
Every country in the free trade era either in the context of multilateral, regional and bilateral is required to improve the competitiveness bacause of the increasing of free trade, tight competition, therefore the policies that have potential to disserve trade and business environment should be minimised. A number of region policy (in the form of tax or Perda of retribution) that burden business environment use the corporate world semejak autonomous region put in place since region autonomy are springing up. Amount of Perda of retribution even tax change quite a lot, which is untill 2006 recorded 9.366 Perda and 962 Reperda. During this time several Perda is still perceived as the main cause of a high cost economy because in the implementation larger than the normal fee and reviewed of several Perda show the  negative impact for the business entire in region. Therefore a review of Perda needs to be done in a comprehensive manner, the evaluation of the implementation also needed to be made in periodically and in addition is giving an award to the region who create a conducive business entire.